Star Clusters A Pocket Field Guide - Cardona III, Charles A.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
Star clusters are some of the most beautiful objects in the night sky and are prime targets for observational astronomers as well as astrophotographers. Using some of the newer technologies and larger and more powerful telescopes available today to amateur astronomers, many more of these dazzling groupings of stars can now be located and viewed throughout the year. In this field guide that will help you to decide what to look for and where to look for it, as well as what equipment to use, you will find what you need, whether you are a beginner in the field or an experienced observer. So on the next clear night, take your book and your binoculars or telescope and maybe your camera outside and see what new wonders can be revealed to you. You won$1 (Bt be disappointed!s
Background -- Understanding Stars and Star Clusters -- How to Use This Book -- Star Cluster -- Descriptions, Images, and Charts.
Keywords: Science (General).; Astronomy; Popular Science; Popular Science in Astronomy; Astronomy, Observations and Techniques